Definición de una guía básica para la creación y desarrollo comercial de una microempresa agropecuaria - Salcedo Muñoz, Virgilio Eduardo (2007)
In the Province of The Oro, and in the country, is formed perma-nently a great quantity of pymes agricultural, the same ones that are born, a great majority grows, but not all stay through the time. The outlined objective was: 1. to settle down and to organize the basic operative elements (administrative, tributary, accountant, marketing and economic) that requires the agricultural pymes to maintain their activity and commercial development, in the Prov-ince of The Oro. To develop the present it guides that he/she orig-inates and it sustains in this study, the available necessary infor-mation was gathered in books, magazines, pamphlets, manuals, laws and Internet, of where you proceeded to revise and later on the information was selected to be used. The necessity was detect-ed of focusing the present study in five basic areas that you/they need the agricultural pymes: tributary, accountant, economic, mar-keting and administrative. Of the work you concluded that that person that wants to create a pymes or that it already possesses a pymes it can adopt the suggestions outlined in this guide, to try to get a better control and commercial development of their business.